Integrative Review: Myths around COVID-19 - Makmun, Armanto; Riyanti, Nabilah; Nurwahyuningsih, Irma (Yayasan Citra Cendekia Celebes, 2022)
Coronaviruses are positive-flavored single-strand RNA viruses from the subfamily Orthocoronavirinae, family Coronaviridae, orders Nidovirales. In December 2019, a group of pneumonia with unknown etiology emerged in Wuhan City, Hubei Province of China. This research aims to look at topics regarding Covid-19, especially issues that develop in society to provide relevant information. This study uses an integrative review method. The source of this research data comes from literature obtained via the internet in the form of research results from international journals in 2020 such as Pubmed, Elsevier, Clinical Key, SCOPUS, American Journal, and others. From a total of 41 journals that the author has reviewed, the conclusion is that sunbathing in the sun or below a temperature above 25C, does not prevent transmission of Covid 19, Covid 19 is not transmitted by mosquito bites, temperature measuring devices cannot determine someone is infected with Covid 19, spray disinfectant on the whole body cannot kill the Coronavirus in the body, eating onions and drinking bleach does not prevent infection from Coronavirus, Covid 19 does not only attack parents but all ages, consuming chloroquine does not prevent Coronavirus infection, Covid 19 transmission does not through eye contact, receiving packages from China is safe and has no potential to transmit Covid 19, and not everyone who is infected with Covid 19 will die. Based on the research results, it was found that there was a lot of misinformation that occurred in the community.